-7+4m=-5+6m

Simple and best practice solution for -7+4m=-5+6m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7+4m=-5+6m equation:


Simplifying
-7 + 4m = -5 + 6m

Solving
-7 + 4m = -5 + 6m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-6m' to each side of the equation.
-7 + 4m + -6m = -5 + 6m + -6m

Combine like terms: 4m + -6m = -2m
-7 + -2m = -5 + 6m + -6m

Combine like terms: 6m + -6m = 0
-7 + -2m = -5 + 0
-7 + -2m = -5

Add '7' to each side of the equation.
-7 + 7 + -2m = -5 + 7

Combine like terms: -7 + 7 = 0
0 + -2m = -5 + 7
-2m = -5 + 7

Combine like terms: -5 + 7 = 2
-2m = 2

Divide each side by '-2'.
m = -1

Simplifying
m = -1

See similar equations:

| 8w-3/2=13-7w-1/8 | | 2/3y-1=7/9 | | 34-4-4b=18 | | 3-(x-4)=2x-6+5x | | 100/6x=79.49 | | 8+(-8)=16 | | 9(x-6)(x+1)=0 | | 5x+2(1-x)=2(2x-4) | | 6y-(y-2)=12/0.064/3 | | 9+v=-5 | | 4p^2-(2p^2-3p+1)= | | 11x-4=10x+5-6 | | x-5/8/2x-10/56 | | 3(x+4)-2(3x-5)+4x-1=4(2x-1)-(2x+5) | | 2x^2=7200 | | 79.49=100/6x | | -7x-27=8-1(1x-19) | | X/9=14/18 | | q^7-9q^5=0 | | ab-4a-4b+8=0 | | 5a+(-7)=-2 | | 4k-7+16=-3 | | 5x+20=24-3x-12 | | 7/(9-5i) | | 2x-4=3(-8-4x) | | 8-3x-(2x-4)=-3 | | (x^2y^3)/xy^4 | | 11/21*42 | | 3x-14y-7x-8y= | | 5910=(13790)r(5) | | (x/3)^2=729 | | a^4+49a^2=0 |

Equations solver categories